Impact of Virtual Reality-Based Training Programs on Employee Skill Development and Job Satisfaction in Technology Industries - Emilianus Eo Kutu Goo; Novi Yanti; Elmira Haci Yusifova (Management Dynamics: International Journal of Management and Digital Sciences, 2024)
The rapid advancements in technology have increased the demand for more efficient and effective training programs, especially in the technology sector. This study explores the impact of Virtual Reality (VR)-based training programs on employee skill development and job satisfaction, comparing them to traditional training methods. A controlled group experiment was conducted with employees from various departments such as IT, software development, and customer service. Participants were randomly assigned to either a VR-based training program or a traditional training program. Data was collected using pre- and post-training surveys to measure changes in employee skills and job satisfaction, as well as interviews to gather qualitative insights into employee experiences. The results revealed that VR training significantly enhanced employee engagement, skill acquisition, and overall job satisfaction. VR-based training allowed employees to engage in practical, hands-on tasks in a controlled, immersive environment, leading to higher motivation and a greater sense of accomplishment. In comparison, traditional training methods did not yield the same level of improvement in engagement or skill development. The study also identified several challenges associated with implementing VR training, including high initial costs, technical limitations, and the learning curve for employees adapting to VR environments. Despite these challenges, the findings suggest that VR training offers substantial benefits in enhancing employee competencies and job satisfaction. The study concludes with recommendations for integrating VR into employee development strategies, especially in technology industries, and proposes further research to explore the long-term impacts and scalability of VR training across different industries.